Counter-rotating wave mode transition dynamics in an RDC. (15th March 2019) - Bluemner, R.; Bohon, M.D.; Paschereit, C.O.; Gutmark, E.J.
Abstract: This work describes an experimental study on the transition dynamics in a hydrogen-air RDC as the operating mode transitions from two steadily propagating, equally-fast counter-rotating waves to a single wave depending on the operating condition. The operating mode for a range of equivalence ratios and mass flow rates is investigated based on time-resolved measurements of the pressure in the combustor annulus at multiple azimuthal locations, as well as based on simultaneous measurements of the natural flame luminosity from the aft end of the RDC. Overall reactant mass flow and equivalence ratio, coupled with the plenum pressures, were confirmed as the driving parameters for wave mode transition. Further experimentation is necessary to decouple these effects, however the results illustrate complex transition dynamics, yielding an acceleration of the primary wave and the simultaneous deceleration of the secondary wave(s). At the same time the secondary wave number is observed to increase up to a triplet of counter-rotating waves. A non-dimensional wave dominance parameter is proposed, which links the relative wave speeds of the waves to thermodynamic properties of the combustor. It indicates regimes of constant wave mode that are independent of changing operating conditions and that extend far into the operating map for the given RDC geometry. The results further indicate a correlation between the operating mode with two counter-rotating waves and choked flames, as well as quasi-detonations observed in generic detonation experiments in the literature. Highlights: An experimental study of different wave modes observed in an H2-air RDC. Results show distinct regimes of operation. CR waves transition to a single wave and are quantified by wave dominance. CR waves propagate at the speed of sound in the products. Sporadic transitions into pairs or triplets of counter-rotating waves.